Full-Factorial Experimental Design to Determine the Impacts of Influential Parameters on the Porosity and Mechanical Strength of LLDEP Microporous Membrane Fabricated via Thermally Induced Phase Separation Method - Shokri, Elham; Yegani, Reza (Journal of Membrane and Separation Technology, 2012)
Membrane separation processes have a wide application in liquid and gas purification industries. They enjoy advantages such as convenient processibility, easy and lower production and operational costs. Thermally induced phase separation (TIPS) process, due to its wide advantages, has won special attention in recent decades. In this process, a homogenous solution of polymer-diluent at a temperature above the polymer melting point is formed and the solution is then cast in the favorite shape. In order to create a porous structure, the diluent is extracted. In this work, microporous LLDPE membrane is fabricated and full factorial experimental design is used to evaluate the individual as well as mutual impacts of polymer concentration, membrane thickness and cooling bath temperature on the porosity and mechanical strength of the membrane. The results obtained from the analysis of variance of membrane porosity and mechanical strength, showed that the impact of cooling bath temperature is much more important than polymer concentration and membrane thickness. Higher cooling bath temperature, lower polymer concentration and membrane thickness result in higher porosity.